Alcoholic drink produced by pea is a risk factor for incident knee surgery in patients with knee osteoarthritis - Huang, Xiaopeng; Zhang, Jinshan; Zheng, Yongqiang; Liu, Xiaofeng; Xu, Yongquan; Fang, Yangzhen; Lin, Zhenyu; Lin, Liang; Zhang, Hongpeng; Wang, Zefeng (Frontiers in Nutrition, 2023)
Objective The objective of this study is to investigate whether alcohol exposure and specific alcoholic drinks are independent risk factors for incident knee surgery in knee osteoarthritis (KOA) patients. Methods We identified all patients who were clinically diagnosed as KOA between January 2010 and January 2018 in our outpatient department. Demographic, clinical, and radiographic data were collected from the database of our hospital. Next, we analyzed the association between alcohol consumption and incident knee surgery. Results A total of 4,341 KOA patients completed the current study and were included in the final analysis. Incident knee surgery for the purpose of treating osteoarthritis was observed in 242 patients. Incident knee surgery was significantly associated with age (OR [95%CI], 1.023 [1.009–1.039], P = 0.002), BMI (OR [95%CI], 1.086 [1.049–1.123], P < 0.001), baseline K-L grade 3 (OR [95%CI], 1.960 [1.331–2.886], P = 0.001), baseline K-L grade 4 (OR [95%CI], 1.966 [1.230–3.143], P = 0.005), 7.1–14 drinks per week (OR [95%CI], 2.013 [1.282–3.159], P = 0.002), >14 standard drinks per week (OR [95%CI], 2.556 [1.504–4.344], P = 0.001), and the most common alcoholic drink produced by pea (OR [95%CI], 3.133 [1.715–5.723], P < 0.001). Conclusion KOA patients who consumed more than seven standard drinks per week were at substantial risk of incident knee surgery. In addition, alcoholic drink produced by pea is also an independent risk factor.